A source of isotopically light organic carbon in a low-pH anoxic marine zone - Vargas, Cristian A.; Cantarero, Sebastian I.; Sepulveda, Julio; Galan, Alexander; De Pol Holz, Ricardo Hernán; Walker, Brett; Schneider, Wolfgang; Farias, Laura; Cornejo D'Ottone, Marcela; Walker, Jennifer; Xu, Xiaomei; Salisbury, Joe (My University, 2021)
Geochemical and stable isotope measurements in the anoxic marine zone (AMZ) off northern Chile during periods of contrasting oceanographic conditions indicate that microbial processes mediating sulfur and nitrogen cycling exert a significant control on the carbonate chemistry (pH, A(T), DIC and pCO(2)) of this region. Here we show that in 2015, a large isotopic fractionation between DIC and POC, a DIC and N deficit in AMZ waters indicate the predominance of in situ dark carbon fixation by sulfur-driven autotrophic denitrification in addition to anammox. In 2018, however, the fractionation between DIC and POC was significantly lower, while the total alkalinity increased in the low-pH AMZ core, suggesting a predominance of heterotrophic processes. An isotope mass-balance model demonstrates that variations in the rates of sulfur- and nitrogen-mediated carbon fixation in AMZ waters contribute similar to 7-35% of the POC exported to deeper waters. Thus, dark carbon fixation should be included in assessments of future changes in carbon cycling and carbonate chemistry due to AMZ expansion.
Keywords: Alkalinity; Autotroph; Carbon fixation; Total inorganic carbon